FAKTOR DOMINAN PENENTU PREFERENSI PEMUKIMAN DI BUKIT GOMBEL KOTA SEMARANG - Saptono Putro; Sriyono Sriyono (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2006)
The research activities are aimed to identify demographic condition and socio-economic, and the activities also determine the factors that are affecting the residence preferences in research areas. The residents ofKelurahan N gesrep Kecamatan Banyumanik as a population, but the data were collected from sample respondents by random tecnique for 3 districts of residential in those areas. The research variable include educational level, income, and socio-cultural etc. (as internal factors) and residence preferences consideration about the location aestetic and prestige, physical and social aspect of the inveronment (as external factors). The data collection method use questionaires and intervews with respondents. The analysis tecniques are descriptive, cross tab analysis and multiple regress. The results show that the spreading of the residents and gender of the research population are indicating a balance proportion and it can said that the educational level is quit high, although the data derived from newcomers. In addition, the income factors are prominent factors in determining residence preferences, especially in location aestetics and prestige (the location coolness and beaty), and the surroundings environments (sanitation and comfort). While the distance factor of the dwelling to the working location is not an important factor to residence preferences. Its interested at building design (house type) as internal factor the realy is dominant prominent factors in determining residential preferences. Based on the research result, we can conclude that : I) there is a balance variation in population distribution, gender, and educational level as well as the economic values offamilies, which are reflected in monthly income level. However, from this condition, we could say that the educational level of the residents in research area are quit high, 2) in residence preferences, newcomers have different characteristics to the origins. The newcomers have chosen the location through careful! planning and consideration, particularly in considering the inverorunent physical and social aspects, 3) the internal factors, that is be interested at building design (house type) is dominant prominent factors in residential preferences.